2013
DOI: 10.1186/1471-2466-13-35
|View full text |Cite
|
Sign up to set email alerts
|

Differences in classification of COPD group using COPD assessment test (CAT) or modified Medical Research Council (mMRC) dyspnea scores: a cross-sectional analyses

Abstract: BackgroundThe GOLD 2011 document proposed a new classification system for COPD combining symptom assessment by COPD assessment test (CAT) or modified Medical Research Council (mMRC) dyspnea scores, and exacerbation risk. We postulated that classification of COPD would be different by the symptom scale; CAT vs mMRC.MethodsOutpatients with COPD were enrolled from January to June in 2012. The patients were categorized into A, B, C, and D according to the GOLD 2011; patients were categorized twice with mMRC and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 18 publications
3
78
0
5
Order By: Relevance
“…Additionally, several groups have demonstrated that the new GOLD multidimensional system classification does not improve prognostic reliability compared with the previous classification based only on spirometric severity for the prediction of mortality and hospitalizations. Indeed, mortality at 3 years was higher in GOLD group B (more symptoms, less risk) than in group C (more risk, fewer symptoms) [17], [36][38]. A possible explanation is that patients in group B have more comorbidities, and therefore more symptoms despite better spirometric values [39]–[40]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several groups have demonstrated that the new GOLD multidimensional system classification does not improve prognostic reliability compared with the previous classification based only on spirometric severity for the prediction of mortality and hospitalizations. Indeed, mortality at 3 years was higher in GOLD group B (more symptoms, less risk) than in group C (more risk, fewer symptoms) [17], [36][38]. A possible explanation is that patients in group B have more comorbidities, and therefore more symptoms despite better spirometric values [39]–[40]…”
Section: Discussionmentioning
confidence: 99%
“…The discordance is deepened further by the fact that dyspnea severity is significantly associated with active smoking. Several studies have cast doubts on the equivalence between dyspnea grade and CAT score in the evaluation of disease involvement 37,38. Indeed, recent evidence shows that the isolated use of CAT as a tool to establish the impact and severity of COPD may be inappropriate, given the difficulty of establishing definite cutoff points for a sufficiently sensitive and specific classification of patients according to their severity 39.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jones et al [6] and Kim et al [7] have shown that a CAT score ≥10 might not be equivalent to an mMRC score ≥2, when classifying patients into low or high symptom groups. To improve the interrater agreement, they suggested using a cut-point of mMRC ≥1 [6, 7]. The present investigation confirmed the fair agreement between CAT and mMRC.…”
Section: Discussionmentioning
confidence: 99%